A proposal for a convertible stadium roof structure derived from Watt-I linkage. Issue 2 (3rd April 2017) - Akgün, Yenal; Gantes, Charis J.; Kalochairetis, Konstantinos E.; Gkagka, Eleftheria E.
ABSTRACT: In this paper, a novel convertible stadium roof structure is introduced, which has been derived from a special geometric configuration of Watt-I linkage, a 1-DoF mechanism used in robot technologies as anthropomorphic fingers. The proposed structure can offer a wide range of different shape configurations according to the environmental conditions and spatial needs, thus offering several aesthetic and functional advantages over existing solutions. This paper serves as a feasibility investigation of this concept, mainly from geometric and structural point of view. To that affect, first kinematic analysis and geometric design of this linkage are introduced. Then, structural analyses of the proposed structure with realistic dimensions and loading conditions are performed in three different geometric configurations, in order to discuss strength and stiffness limitations. Finally, potential cover materials and actuators are briefly discussed.